LL(1) cannot be ambiguous

后端 未结 3 2056
栀梦
栀梦 2021-02-20 00:30

How can it be shown that no LL(1) grammar can be ambiguous?

I know what is ambiguous grammar but could not prove the above theorem/lemma.

相关标签:
3条回答
  • 2021-02-20 01:07

    Here's my first draft at a proof. It might need some fine tuning, but I think it covers all the cases. I think many solutions are possible. This is a direct proof.

    (Side note: it is a pity SO doesn't support math, such as in LaTeX.)

    Proof

    Let T and N be the sets of terminal and non-terminal symbols.

    Let the following hold

    MaybeEmpty(s) = true <=> s ->* empty
    First(s) = X containing all x for which there exists Y such that s ->* xY
    Follow(A) = X containing all x for which there exists Y,Z such that S ->* YAxZ
    

    Note that a grammar is LL(1) if the following holds for every pair of productions A -> B and A -> C:

    1. (not MaybeEmpty(B)) or (not MaybeEmpty(C))
    2. (First(B) intersect First(C)) = empty
    3. MaybeEmpty(C) => (First(B) intersect Follow(A)) = empty
    

    Consider a language with is LL(1), with A -> B and A -> C. That is to say there is some string of terminals TZ which admits multiple derivations by distinct parse trees.

    Suppose that the left derivation reaches S ->* TAY ->* TZ. The next step may be either TAY -> TBY, or TAY -> TCY. Thus the language is ambiguous if both BY ->* Z and CY ->* Z. (Note that since A is an arbitrary non-terminal, if no such case exists, the language is non-ambiguous.)

    Case 1: Z = empty

    By rule 1 of LL(1) grammars, at most one of B and C can derive empty (non-ambiguous case).

    Case 2: Z non-empty, and neither B nor C derive empty

    By rule 2 of LL(1) grammars, at most one of B and C can permit further derivation because the leading terminal of Z cannot be in both First(B) and First(C) (non-ambiguous case).

    Case 3: Z non-empty, and either MaybeEmpty(B) or MaybeEmpty(C)

    Note the by rule 1 of LL(1) grammars, B and C cannot both derive empty. Suppose therefore that MaybeEmpty(C) is true.

    This gives two sub-cases.

    Case 3a: CY -> Y; and Case 3b: CY ->* DY, where D is not empty.

    In 3a we must choose between BY ->* Z and CY -> Y ->* Z, but notice that First(Y) subset-of Follow(A). Since Follow(A) does not intersect First(B), only one derivation can proceed (non-ambiguous).

    In 3b we must choose between BY ->* Z and CY ->* DY ->* Z, but notice that First(D) subset-of First(C). Since First(C) does not intersect First(B), only one derivation can proceed (non-ambiguous).

    Thus in every case the derivation can only be expanded by one of the available productions. Therefore the grammar is not ambiguous.

    0 讨论(0)
  • 2021-02-20 01:19

    Prove that no ambiguous grammar can be an LL(1) grammar. For hints, see http://www.cse.ohio-state.edu/~rountev/756/pdf/SyntaxAnalysis.pdf, slides 18-20. Also see http://seclab.cs.sunysb.edu/sekar/cse304/Parse.pdf, pg. 11 and preceding.

    0 讨论(0)
  • 2021-02-20 01:22

    I think it's nearly a direct result of the definition of LL(1). Try proof by contradiction; assume that you have an LL(1) grammar that is ambiguous and look for something you can show to be true and not true. As a starting point "what do you always know as you process input?"

    As this seems like a homework problem and I actually haven't finished the problem any more than I sketched out above, I'll stop there.

    0 讨论(0)
提交回复
热议问题